THE ASSESSMENT OF COMPLIANCE TO THE USE OF NEW ORAL ANTICOAGULANTS IN PATIENTS WITH ATRIAL FIBRILLATION ACCORDING TO THE PROFILE REGISTER - S. Y. Martsevich; A. R. Navasardyan; N. P. Kutishenko; A. V. Zakharova; V. P. Voronina; N. A. Dmitrieva; L. Yu. Lrozdova; A. V. Zagrebelnyy; O. V. Lerman; Yu. V. Lukina; G. V. Martynova; A. A. Nikulina; et al. (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study in the PROFILE register the rate of new oral anticoagulants (NOAC) taking in patients with atrial fibrillation (AF) and to identify the factors influencing it.Material and methods. Patients with AF who applied to the Cardiology Center in 2013-2014 (n=111) were included into the study. The oral anticoagulants (OAC) were recommended to patients at the reference visit (n=97). Inquiry in questionnaire format was performed to assess the compliance to recommended therapy at the follow-up visit. Patients were divided into two groups according to taking/not-taking NOAC. Analysis of the facts that influence the compliance to NOAC therapy was performed.Results. At the reference visit 70 patients desired to receive NOAC. At the follow-up visit 29 (41.4%) patients refused to take NOAC. Leading causes of NOAC refusal were satisfactory with warfarin (32.6%), the high price of these drugs (23.9%), the description of adverse reactions in the patient information leaflet for medicines (15.2%), and withdrawal by physician in outpatient clinic/hospital (8.7%). Preferential provision of medicines and warfarin therapy at the time of reference visit had a negative impact on the taking of NOAC. Patients taking NOAC were more aware of the possible outcomes of their illness, the possible side effects of OAC and were more familiar with patient information leaflet for medicines.Conclusion. The study assessed NOAC taking rate and the factors influencing patients' compliance to NOAC therapy.